Press and ethnic polarization in post-2001 Afghanistan: the 2014 presidential election experience. Issue 1 (2nd January 2016) - Sahar, Arif; Sahar, Aqila
Abstract : This article analyses the contents of three newspapers affiliated with the Tajik-dominated Jamiat and Shura-e-Nezar factions that were deployed during the 2014 presidential election to publicize ethno-political polarization for instrumental ends. The practice of nurturing ethnic identities serves as a microcosm of the broader context in which identity politics, besides coalition-building, rent-seeking, and patrimonial interdependencies, has become a key feature of post-2001 politics. This article focuses on how these factions used these newspapers to polarize ethnic cleavages to win legitimacy for themselves and defamation for their Pashtun-dominated rival factions – Hezb-e-Islami Gulbuddin and the Taliban. It will be years before the ethnic mujahedeen and muhajereen and the new generation reach a mutually binding and working condition that facilitates the country's long-term stability. Reaching this condition is critical because the future of Afghanistan lies in the commitment of its people to form a united community that resolves disputes in the manner of a democratic nation.